Предмет: Алгебра, автор: 828384

frac{1}{6 sqrt{32} } - frac{6* sqrt{32}+ frac{1}{8} }{6* sqrt{32}* frac{1}{8 } }

Ответы

Автор ответа: zhenyaM2002
0
 frac{1}{6 sqrt{32} }  -  frac{6 sqrt{32}+  frac{1}{8}  }{6 sqrt{32} * frac{1}{8} } =  frac{ frac{1}{8} -( 6 sqrt{32}+  frac{1}{8})}{6 sqrt{32}*  frac{1}{8}  } =  \  \ 
=frac{ frac{1}{8} - 6 sqrt{32}-  frac{1}{8}}{6 sqrt{32}*  frac{1}{8}  } =  frac{- 6 sqrt{32}}{6 sqrt{32}*  frac{1}{8} } = frac{-1}{ frac{1}{8} } =  \  \ 
= -1  *  frac{8}{1} = -8
Похожие вопросы
Предмет: Алгебра, автор: cloudyPWNZ